The impact of electronic accounting disclosure on the quality of accounting information: An applied study on commercial banks in Sudan - Bahreldin, Nagwa Mohamed (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to identify the impact of electronic accounting disclosure on the quality of accounting information for commercial banks in Sudan . The study relied on the descriptive analytical approach, the inductive approach, and the historical approach. The questionnaire was used as a primary source to obtain the data . The study reached several results, the most important of which are: There is a direct relationship between electronic accounting disclosure and the quality of accounting information, as electronic accounting disclosure contributes an effective role in enhancing and increasing the utility and quality of accounting information, and electronic accounting disclosure contributes to providing accounting information to its users at the appropriate time to take Appropriate decisions. The study recommended a number of recommendations, including: the need to pay attention to the quality of accounting information published electronically to support the confidence and credibility of users of this information. Continuously qualifying and training accountants, auditors and workers in the banking sector in the field of information technology to hone their skills and enhance their knowledge and abilities, and the need to pay attention to the security and safety procedures of websites and the provisions of control over them.
Keywords: electronic accounting disclosure; quality of accounting information; transparency; suitability; reliability